2009
DOI: 10.3174/ajnr.a1441
|View full text |Cite
|
Sign up to set email alerts
|

Comparing and Predicting the Costs and Outcomes of Patients with Major and Minor Stroke Using the Boston Acute Stroke Imaging Scale Neuroimaging Classification System

Abstract: BACKGROUND AND PURPOSE:A neuroimaging-based ischemic stroke classification system that predicts costs and outcomes would be useful for clinical prognostication and hospital resource planning. The Boston Acute Stroke Imaging Scale (BASIS), a neuroimaging-based ischemic stroke classification system, was tested to determine whether it was able to predict the costs and clinical outcomes of patients with stroke at an urban academic medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
2
22
0
1
Order By: Relevance
“…The correlations were not very strong, a point largely reported in the literature [22][23][24] and easy to understand, considering the numerous additional factors that can influence clinical outcomes at the disability/handicap level (On-line Fig 1). [25][26][27] Here, other clinical (initial stroke severity, age) or neuroimaging (recanalization, reperfusion) variables were significantly associated with the outcome, in line with previous studies. 25,28 The relatively weak association between infarct volumes and clinical outcomes does not necessarily discredit volume as a surrogate marker.…”
Section: Discussionsupporting
confidence: 76%
“…The correlations were not very strong, a point largely reported in the literature [22][23][24] and easy to understand, considering the numerous additional factors that can influence clinical outcomes at the disability/handicap level (On-line Fig 1). [25][26][27] Here, other clinical (initial stroke severity, age) or neuroimaging (recanalization, reperfusion) variables were significantly associated with the outcome, in line with previous studies. 25,28 The relatively weak association between infarct volumes and clinical outcomes does not necessarily discredit volume as a surrogate marker.…”
Section: Discussionsupporting
confidence: 76%
“…Second, numerous studies have identified stroke severity to be the most important determinant of resource use in the treatment of stroke patients [32,33,34,35,36,37]. However, stroke severity is not included as a classification variable in any of the DRG systems analysed.…”
Section: Discussionmentioning
confidence: 99%
“…If there is much variation in LoS between units, or if the LoS averages differ substantially, it raises the question whether the treatment is optimally managed in all units. For cerebral infarction, LoS is a strong indicator for the costs of treatment (Cipriano et al, 2009;Diringer et al, 1999;Saxena et al, 2006;Seitz and Edwardson, 1987). Therefore, any unwarranted upward variation in LoS also implies undesirable variation in costs and inefficient use of resources.…”
Section: Introductionmentioning
confidence: 99%